Change in community behaviour in supporting sustainable development: The case of the biogas program in Ponorogo Regency - Agustin, Dinda Putri; Nurwati, Nunung; Lesmana, Aditya Candra (Jurnal Sosiologi Dialektika, 2024)
The change in community occupation to dairy farmers and the increase in the number of livestock have caused environmental problems. This research focuses on the program’s function on changing the behaviour of the community in disposing of dairy cow manure from the phase of throwing it into the ditch to the phase of processing the manure into the biogas. This research was conducted using qualitative methods, with data collection techniques carried out through in-depth interviews, observation, documentation and literature review. The biogas problem launched by the government has proven to be able to change communities behaviour in the disposal of dairy cows manure. After receiving the biogas program, the community processed the cow dung into biogas. Interestingly, the factor that contributed the most to this behavioural change is economic. This shows that the social, environmental, and economic system have related functions and cannot be separated from each other in society. There is not much research on community behaviour change that is affected by environmental sanitation and motivated by economic factors. This study also alludes to the potential for corruption in the program. This study concludes that the biogas program is able to provide opportunities for the community to save on purchasing household fuel and minimize the waste of dairy cow waste into rivers. Apart from that, the biogas program could be a consideration for the government in creating new programs related to environmental sanitation, especially in the rural livestock industry.